Agreement of glaucoma specialists and experienced optometrists in gonioscopy and optic disc evaluation - Kumar, Addepalli U. (2013)
PURPOSE: To compare the diagnostic performance of glaucoma specialists and experienced optometrists in gonioscopy and optic disc assessment. METHODS: This study was done to validate the diagnostic performance of two experienced optometrists for using their skills of detecting glaucoma using gonioscopy and optic disc assessment in a major epidemiological study, the L V Prasad Eye Institute Glaucoma Epidemiology and Molecular Genetics Study (LVPEI-GLEAMS). Gonioscopic findings for 150 eyes were categorized as 0, 1 and 2 for open angle, primary angle closure suspect (PACS) and primary angle closure (PAC) respectively. Optic disc findings for 200 eyes were categorized as 0, 1 and 2 for normal, suspects and glaucomatous respectively. Weighted kappa (κ) and diagnostic accuracy parameters were calculated. Two optometrists (#1 and #2) participated in the study. RESULTS: Agreement between glaucoma specialists and optometrist for interpretation of gonioscopy to discriminate PACS and PAC from open angles and for interpretation of optic disc to discriminate glaucomatous and suspicious discs from normal, the kappa (κ) was 0.92 and 0.84 and 0.90 and 0.89 for optometrists #1 and #2 respectively. Sensitivities and specificities were above 90% for gonioscopy. Optic disc evaluation had specificities greater than 95% to discriminate normal from glaucomatous discs while the sensitivities were 83% and 93% for optometrists #1 and #2 respectively. CONCLUSION: Agreement between optometrists and glaucoma specialists, in diagnostic performance of gonioscopy and optic assessment was excellent with high sensitivity and specificity. Hence, we conclude that the experienced optometrists can detect glaucoma accurately in the LVPEI-GLEAMS.